Perturbations in the A1Π, v = 0 state of 12C18O investigated via complementary spectroscopic techniques. (17th December 2017) - Trivikram, T. Madhu; Hakalla, R.; Heays, A. N.; Niu, M. L.; Scheidegger, S.; Salumbides, E. J.; de Oliveira, N.; Field, R. W.; Ubachs, W.
ABSTRACT: The A 1 Π( v = 0) level of 12 C 18 O has been reinvestigated using three different high-resolution spectroscopic methods: (1) 2 + 1′ resonance-enhanced multiphoton ionisation of the A 1 Π − X 1 Σ + (0, 0) band using narrowband lasers in a Doppler-free geometry; (2) Fourier-transform emission spectroscopy in the visible range probing the B 1 Σ + − A 1 Π(0, 0) band in a discharge; (3) Fourier-transform absorption spectroscopy in the vacuum-ultraviolet range measuring the A 1 Π − X 1 Σ + (0, 0) and B 1 Σ + − X 1 Σ + (0, 0) bands at multiple temperatures ranging from 90 to 900 K. An effective-Hamiltonian analysis of A 1 Π, v  = 0 levels was performed up to J = 44 which quantitatively addresses perturbations by the e  3 Σ − ( v  = 1), d 3 Δ( v  = 4), a′ 3 Σ + ( v  = 9), D  1 Δ( v  = 0), and I  1 Σ − ( v  = 0, 1) levels. Abstract :